THE ROLE OF VOLUNTEERING IN THE FORMATION OF STUDENTS’ HUMANISTIC VALUES - Arzu Qasımov; Taleh Khalılov (International Journal of Innovative Technologies in Social Science, 2025)
This article explores the role of volunteering in the formation of students’ humanistic values. Volunteering positively influences the development of social responsibility, empathy, compassion, cooperation, and solidarity. By participating in volunteer activities, students learn to contribute to society, gain a deeper understanding of social issues, and develop a habit of helping others. The article highlights that volunteering plays a significant role in students’ personal development and increases their social engagement. These activities expand their worldview, enhance leadership, communication, and teamwork skills, and instill a sense of responsibility. Moreover, volunteering strengthens students’ social integration and fosters a sense of belonging within the community. The study concludes that volunteering is crucial in enriching students with humanistic values. Such activities have a significant impact not only on the education system but also on the overall development of society. Therefore, encouraging students to engage in volunteer work is essential for their personal growth and social progress.